PENGEMBANGAN MODUL DIGITAL INTERAKTIF BERBASIS SELF-LEARNING PADA MATA KULIAH KARYA TULIS ILMIAH - Suarlin; Bhakti Prima Findiga Hermuttaqien; Iwan Setiawan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
In the current era, lecturers and teachers need to pay more attention to the Industry 4.0 revolution by developing innovative and creative technology-based learning media to enhance teaching and learning activities. This research aims to develop a self-learning-based interactive digital module for Scientific Paper subjects, conducted at Universitas Negeri Makassar in November 2021. The research employed a Research and Development (R&D) design. Data were collected using observations, questionnaires, and interviews and analyzed through qualitative and quantitative approaches. The results indicate that the developed self-learning-based interactive digital module is highly feasible. Evaluation from media experts during the alpha test yielded 90.62% (“very feasible”), material experts provided 90.51% (“very feasible”), and user assessment during the beta test obtained 94.01% (“very feasible”). Therefore, the interactive digital module is highly suitable for use as a learning medium for PGSD students.